Flexible, Luminescent Metal–Organic Frameworks Showing Synergistic Solid‐Solution Effects on Porosity and Sensitivity. (28th November 2016) - Liu, Si‐Yang; Zhou, Dong‐Dong; He, Chun‐Ting; Liao, Pei‐Qin; Cheng, Xiao‐Ning; Xu, Yan‐Tong; Ye, Jia‐Wen; Zhang, Jie‐Peng; Chen, Xiao‐Ming
Abstract: Mixing molecular building blocks in the solid solution manner is a valuable strategy to obtain structures and properties in between the isostructural parent metal–organic frameworks (MOFs). We report nonlinear/synergistic solid‐solution effects using highly related yet non‐isostructural, phosphorescent Cu I triazolate frameworks as parent phases. Near the phase boundaries associated with conformational diversity and ligand heterogeneity, the porosity (+150 %) and optical O2 sensitivity (410 times, limit of detection 0.07 ppm) can be drastically improved from the best‐performing parent MOFs and even exceeds the records hold by precious‐metal complexes (3 ppm) and C70 (0.2 ppm).